Determinants of Employee Performance are mediated by Productivity University in Jakarta - WULANDARI, SRI; MANURUNG, ADLER HAYMANS; HENDAYANA, YAYAN (Journal of Ecohumanism, 2024)
This research aims to determine and analyze the influence of recruitment analysis, training and development, employee involvement, and technology adoption on employee performance which is mediated by productivity among employees at University in Jakarta. The method used in this research is a quantitative method with survey techniques, where the population used as subjects in the research are employees at University in Jakarta, with a sample size of 172 people. Data analysis uses Structural Equation Modeling (SEM) with the help of SmartPLS. The research results show that recruitment analysis, employee involvement, and technology adoption have an influence on productivity. while training and development has no effect on productivity. Recruitment analysis and technology adoption influence employee performance. Meanwhile, development training and employee involvement have no effect on employee performance. Productivity influences employee performance, but does not act as a mediating variable. This research has significant novelty both in terms of research topic, number of variables studied, and research locus.